Enhancement of Transient Stability and Power Quality in Grid-Connected PV Systems Using SMES - Heroual, Samira; Belabbas, Belkacem; Elzein, I. M.; Diab, Yasser; Ma'arif, Alfian; Mahmoud, Mohamed Metwally; Allaoui, Tayeb; Benabdallah, Naima (International Journal of Robotics and Control Systems, 2025)
One of the main issues with grid-connected distributed energy systems, including photovoltaic (PV) systems, is the DC bus voltage's instability during load fluctuations and power line short circuits. This paper attempts to address this problem and proposes to use superconducting magnetic energy storage (SMES) to stabilize the voltage of the DC link and improve the power quality and transient stability of the power system. The investigated configuration components are PV cells, boost converter, chopper, SMES, three level inverter (NPC), filter, grid, and load. MATLAB / Sim Power System is used to test the performance of a SMES in order to ensure the balance of the DC bus voltage of a PV system connected to the grid. Several scenarios were considered to show the performance and benefits of combining a SMES with the PV system. The outcomes of the examined scenarios (fault and load change) demonstrate the precision of the employed control systems, maintaining the DC voltage at acceptable levels (?500 V), enhances the structure stability, and improving power quality (GPV THD = 4.34). Finally, it can be concluded that the proposed configuration will help in achieving high penetration scenarios of PV systems.